The Role of Autoimmune Regulator (AIRE) in Peripheral Tolerance - Bingjie Zhao; Lu Chang; Haiying Fu; Guangyu Sun; Wei Yang (Journal of Immunology Research)
Autoimmune regulator (AIRE), whose gene mutation is considered to be a causative factor of autoimmune polyglandular syndrome type 1 (APS1), is an important transcriptional regulator. Studies on the role of AIRE in the central immune system have demonstrated that AIRE can eliminate autoreactive T cells by regulating the expression of a series of tissue specific antigens promiscuously in medullary thymic epithelial cells (mTECs) and induce regulatory T cell (Treg) production to maintain central immune tolerance. However, the related research of AIRE in peripheral tolerance is few. In order to understand the current research progress on AIRE in peripheral tolerance, this review mainly focuses on the expression and distribution of AIRE in peripheral tissues and organs, and the role of AIRE in peripheral immune tolerance such as regulating Toll-like receptor (TLR) expression and the maturation status of antigen presenting cells (APCs), inducing T cell tolerance and differentiation. This review will show us that AIRE also plays an indispensable role in the periphery.